Pulmonary schistosomiasis mimicking IgG4‐related lung disease. Issue 1 (16th October 2017) - Baird, Timothy; Cooper, Caroline L; Wong, Richard; Runnegar, Naomi; Keir, Gregory
Abstract : IgG4‐related disease (IgG4‐RD) is a systemic fibroinflammatory disease characterized by tumefactive lesions in various organ systems, including the lungs. Clinical and radiological manifestations of IgG4‐RD are relatively non‐specific, and we report a case highlighting the importance of histopathological confirmation in cases of suspected IgG4‐related lung disease. A 44‐year‐old male with significantly elevated serum IgG4 levels, patchy consolidation on thoracic CT imaging, and cough was referred with suspected IgG4‐related lung disease. However, surgical lung biopsy revealed an unexpected diagnosis of pulmonary schistosomiasis, and following treatment with praziquantel, cough resolved and IgG4 levels significantly declined. This case highlights the potentially diverse array of conditions that may mimic IgG4‐related lung disease and the importance of comprehensive evaluation including histopathological confirmation where possible. Abstract : We report a case of a 44‐year‐old male referred with suspected IgG4 related lung disease that highlights the importance of a comprehensive clinical assessment, including a confirmatory tissue biopsy. Despite elevated serum IgG4 levels coupled with suggestive symptoms and radiologic changes, a surgical lung biopsy revealed an unexpected diagnosis of pulmonary schistosomiasis.